Labyrinth [videorecording (DVD)] - Jones, Terry, 1942-2020; Lee, Dennis, 1939-; Bowie, David; Connelly, Jennifer; Thompson, Shelley (Sony Pictures Home Entertainment, 2016)
Babysitting infant stepbrother Toby on a weekend night isn't young Sarah's idea of fun. Frustrated by his crying, she secretly imagines the Goblins from her favorite book, Labyrinth, carrying Toby away. When her fantasy comes true, a distraught Sarah must enter a maze of illusion to bring Toby back from a kingdom inhabited by mystical creatures and governed by the wicked Goblin King.